Diagnosis and Treatment of Pain in Small Fiber Neuropathy - Hovaguimian, Alexandra (2011)
Small fiber neuropathy manifests in a variety of different diseases and often results in symptoms of burning pain, shooting pain, allodynia, and hyperesthesia. Diagnosis of small fiber neuropathy is determined primarily by the history and physical exam, but functional neurophysiologic testing and skin biopsy evaluation of intraepidermal nerve fiber density can provide diagnostic confirmation. Management of small fiber neuropathy depends on the underlying etiology with concurrent treatment of associated neuropathic pain. A variety of recent guidelines propose the use of antidepressants, anticonvulsants, opioids, topical therapies, and nonpharmacologic treatments as part of the overall management of neuropathic pain. Unfortunately, little data about the treatment of pain specifically in small fiber neuropathy exist because most studies combine mixed neuropathic pain syndromes in the analysis. Additional studies targeting the treatment of pain in small fiber neuropathy are needed to guide decision making.